FINANCIAL MECHANISMS OF THE FUNCTIONING OF INNOVATION PARKS IN THE CONDITIONS OF INDUSTRY 4.0 - Крисоватий, Ігор Андрійович (Journal of Strategic Economic Research, 2024)
The presented work emphasizes that in the context of the transition to Industry 4.0, the financial mechanisms for the functioning of innovation parks become a critically important element for ensuring the effective development of technological innovations and support for startups. Industry 4.0, which is characterized by the introduction of modern technologies such as the Internet of Things, artificial intelligence, big data and automation, requires new approaches to the organization and financing of innovative activities. That is why the purpose of the presented work is to determine the features of the financial mechanisms of the functioning of innovation parks in the conditions of Industry 4.0. The main methods presented in the work were: the synthesis method, the induction method, the analysis method, the generalization method, the deduction method, the analytical method, the logical method, the comparison method, and the graphic method. The presented set of methods for the study made it possible to form the current framework of the study. As a result of the conducted research, it is possible to emphasize that innovation parks, as specialized infrastructural and organizational platforms for the development and commercialization of innovations, play the role of catalysts of technological progress and economic growth. They unite research institutes, start-ups, industrial enterprises and investors in a single ecosystem, which promotes faster introduction of new technologies and products. At the same time, the financial mechanisms that support these innovative ecosystems include a variety of tools and strategies, such as venture capital, crowdfunding, government grants, private investments and partnerships with financial institutions. In the context of Industry 4.0, these mechanisms are becoming increasingly complex and multifaceted, as investment and financing requirements change along with the development of new technologies. In order to support the effective functioning of innovation parks, it is important not only to understand the specifics and nature of these financial instruments, but also to consider the impact they have on the overall development of the innovation ecosystem. This includes both economic aspects and issues of managerial and organizational approaches to the implementation of innovative projects. During the study, effective financing strategies that contribute to the successful development of technologies and startups were also identified, as well as to identify the challenges and opportunities facing the participants of innovative ecosystems in the new technological reality.